Mental health care policy reform in Turkey: User group perspectives - Bilir, Merve Kardelen. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
The mental health policy of Turkey has been undergoing a transformation process since 2006. The main aim of this change is to prioritize the establishment of community-based mental health care services and to organize an accessible mental healthcare service network across the country. In this regard, this thesis explores the politics of mental health policy change in Turkey through a qualitative analysis of the views of mental health user groups on these changes. The main objective of this thesis is to analyze the politics of mental health policy change in Turkey and to understand the role of user groups in this process by a qualitative analysis of the views of mental health user groups on these transformations. There are 13 in-depth semi-structured interviews in this thesis that were conducted with representatives of mental health user groups in Ankara, Istanbul and Izmir between April and June 2018. The thesis reveals that this policy change took the form of the balanced care model, and the introduction of community-based mental health care centers provided to increase the utilization of mental health care services. However, it is not sufficient to bring a holistic view of the Turkish mental health system, which provides recovery-based services through medical and social support to empower individuals living with mental health issues. In addition, the user group representatives were included in this study believe that this policy change did not meet the expectations of user groups and remained insufficient in other respects.
Keywords: Mental health services -- Turkey.; Mental health policy -- Turkey.